The role of incidence angle in the morphology evolution of Ge surfaces irradiated by medium-energy Au ions. (19th July 2018) - Dell'Anna, Rossana; Iacob, Erica; Barozzi, Mario; Vanzetti, Lia; Hübner, René; Böttger, Roman; Giubertoni, Damiano; Pepponi, Giancarlo
Abstract: Germanium (Ge) surfaces have been irradiated with 26 keV gold (Au) ions at a constant fluence and at incidence angles varying from 0° to 85°. The evolution of the emerging nanostructures is studied by atomic force microscopy (AFM), scanning electron microscopy, x-ray photoelectron spectroscopy (XPS), and cross-sectional transmission electron microscopy. The obtained results are compared with findings reported in the literature. Periodic rippled patterns with the wave vector parallel to the projection of the ion beam direction onto the Ge surface develop between 30° and 45°. From 75° the morphology changes from parallel-mode ripples to parallel-mode terraces, and by further increasing the incidence angle the terraces coarsen and show a progressive break-up of the front facing the ion beam. No perpendicular-mode ripples or terraces have been observed. The analysis of the AFM height profiles and slope distributions shows in the 45°–85° range an angular dependence of the temporal scale for the onset of nonlinear processes. For incidence angles below 45°, the surface develops a sponge-like structure, which persists at higher incidence angles on the top and partially on the face of the facets facing the ion beam. The XPS and the energy-dispersive x-ray spectroscopy evidence the presence of Au nano-aggregates of different sizes for the different incidence angles. This study points out the peculiar behavior of Ge surfaces irradiated with medium-energy Au ions and warns about the differences to be faced when trying to build a universal framework for the description of semiconductor pattern evolution under ion-beam irradiation.